2015
DOI: 10.1016/j.neuroimage.2015.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Domain-general involvement of the posterior frontolateral cortex in time-based resource-sharing in working memory: An fMRI study

Abstract: Working memory is often defined in cognitive psychology as a system devoted to the simultaneous processing and maintenance of information. In line with the time-based resource-sharing model of working memory (TBRS; Barrouillet and Camos, 2015;Barrouillet et al., 2004), there is accumulating evidence that, when memory items have to be maintained while performing a concurrent activity, memory performance depends on the cognitive load of this activity, independently of the domain involved. The present study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…While the cognitive-load effect has mainly appeared in serial recall tasks such as complex span tasks (Barrouillet et al, 2004(Barrouillet et al, , 2007(Barrouillet et al, , 2011Vergauwe et al, 2009Vergauwe et al, , 2010Vergauwe et al, , 2012 and Brown-Peterson tasks (Liefooghe et al, 2008), it has also been obtained in single-item recall or local recognition tests (Ricker & Cowan, 2010;Vergauwe et al, 2009;Vergauwe, Hartstra, Barrouillet, & Brass, 2015) and change detection tasks (Vergauwe et al, 2014). was estimated by the ratio of total processing time on the parity or location judgments (i.e., the sum of response times) to total time (i.e., the sum of the time intervals for each judgment).…”
Section: Multiple-task Effectsmentioning
confidence: 99%
“…While the cognitive-load effect has mainly appeared in serial recall tasks such as complex span tasks (Barrouillet et al, 2004(Barrouillet et al, , 2007(Barrouillet et al, , 2011Vergauwe et al, 2009Vergauwe et al, , 2010Vergauwe et al, , 2012 and Brown-Peterson tasks (Liefooghe et al, 2008), it has also been obtained in single-item recall or local recognition tests (Ricker & Cowan, 2010;Vergauwe et al, 2009;Vergauwe, Hartstra, Barrouillet, & Brass, 2015) and change detection tasks (Vergauwe et al, 2014). was estimated by the ratio of total processing time on the parity or location judgments (i.e., the sum of response times) to total time (i.e., the sum of the time intervals for each judgment).…”
Section: Multiple-task Effectsmentioning
confidence: 99%
“…STM of an item has been thought to remain stable for as long as attention is sustained. Elapsing time has often been considered responsible for the decay of information over a retention interval, with evidence supporting models based on rehearsal [ 41 ], or drift [ 42 ] and extinction [ 43 ] in neural representations. Against this, it has been shown that memory decay can be reduced if the gap between trials (when nothing is happening) is much longer than the retention interval [ 44 ].…”
Section: Stm For Timementioning
confidence: 99%
“…The effect of increasing cognitive load also has a different neural signature. Cognitive load in general modulates the activity of superior parietal lobule and intraparietal sulcus bilaterally, and particularly of the right inferior frontal junction ( Vergauwe et al. 2015 ).…”
Section: Automatic Versus Deliberately Controlled Processes: Type 1 Vmentioning
confidence: 99%